Toy collections in private preschools in Marikina City management policies and practices - Orocay, Anna Liza G.; Gonzales, Grace Marie B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
More and more libraries are incorporating toys in their collection today. Mainly, this study aims to examine the management policies and practices of toy collections in preschool libraries, specifically, the organization and arrangement of toys in the collection, policies and practices on collection development, as well as the utilization and maintenance of the toy collection. From the documentation of management practices and policies of different libraries involved, this study will provide guidelines and insights to improve the management of the toy collection in a library, thus providing ways to better serve its users.
The respondents of the study are the private preschool libraries in Marikina City which house a collection of toys that are readily accessible to its users. The study utilized the descriptive survey method. The questionnaire is used as the principal instrument for gathering data and ocular inspection and follow-up interviews for data supplementation.
Major findings of the study are the following: a. Most of the private preschool libraries do not have librarians. The management of the toy collection in private preschool libraries is a collaboration between the school head/principals and the preschool teacher. b. The libraries do not have a written policy or guidelines for collection development of toys. However, the libraries practice a more or less common and simple unwritten policy for collection development of toys as they continuously develop their collection and it is the school principal/head alongside with the teachers who are involved in this activity (selection, acquisition and deselection) c. The toy collection of private preschool libraries are poorly organized. Most of the libraries do not use a classification system for the collection. The toys are not catalogued although some libraries keep an updated inventory list of materials. d. The students and the teachers are the users of the toy collection among the libraries. The libraries do not loan their toys for home use and can only be used by children within the library or school premises supervised by teachers. Permit from teachers are required for students to access the collection. e. The teachers alongside with teacher aides and maintenance personnel/helper are responsible for collection maintenance. The cleaning and sterilization of toys in the collection are done weekly by most of the libraries. Inventory of materials with broken parts is done annually while repairing of materials with broken or lost part is done daily. Washing with water and soap/detergent is the common process of cleaning and sterilization of toys. Materials which have broken or lost parts are repaired if possible and in cases that it is not, these are disposed or replaced.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries and preschool children -- Philippines -- Marikina City; Preschool children -- Services for -- Philippines -- Marikina City